2015
DOI: 10.1039/c5nr05904f
|View full text |Cite
|
Sign up to set email alerts
|

Facile production of monodisperse nanoparticles on a liquid surface

Abstract: The emergence of monodispersity during particle growth on a liquid substrate was investigated both by experimental methods and by computer simulation. Monodispersity arises through a novel mechanism (termed "shared coarsening"), associated with the spatial distribution of the particles; smaller particles are simultaneously consumed by several larger particles. Particle monodispersity was predicted by kinetic Monte Carlo simulation for suitable substrate adsorption probability and adatom diffusion length condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
3
1
Order By: Relevance
“…This is, however, in direct contradiction with a number of studies that have found the sputtering time not essentially important with respect to size and distribution [39]. This can be explained by the fact that the model published by Anantha et al [38] does not reflect changes in concentration throughout the whole volume of the liquid. During deposition, the deposited material accumulates at the liquid-vacuum interface (or at a small depth below the surface).…”
Section: Metal Nanoparticles In Liquids: Preparation Fundamentalscontrasting
confidence: 61%
See 1 more Smart Citation
“…This is, however, in direct contradiction with a number of studies that have found the sputtering time not essentially important with respect to size and distribution [39]. This can be explained by the fact that the model published by Anantha et al [38] does not reflect changes in concentration throughout the whole volume of the liquid. During deposition, the deposited material accumulates at the liquid-vacuum interface (or at a small depth below the surface).…”
Section: Metal Nanoparticles In Liquids: Preparation Fundamentalscontrasting
confidence: 61%
“…A more detailed view into the formation mechanism of NPs was provided by Anantha et al [38]. They describe the process of preparing uniform NPs using a so-called shared coarsening model.…”
Section: Metal Nanoparticles In Liquids: Preparation Fundamentalsmentioning
confidence: 99%
“…Besides chemical syntheses, there have been reports recently of successful preparation of metal nanoparticles and related composites via physical vapor deposition (PVD) onto liquids with very low vapor pressures, such as silicone oils, vegetable oils, poly­(ethylene glycol), , liquid crystals, and room temperature ionic liquids (RTILs), in which small clusters or atoms ejected from bulk metals were trapped on the liquid surface and then formed islandlike aggregates of metal particles on the liquid surface or nanoparticles uniformly dispersed in the bulk liquid phase. RTILs are particularly useful for the synthesis of nanoparticles with well-controlled sizes and shapes, because of their extremely low vapor pressure and their capabilities to dissolve many kinds of substances and to uniformly disperse a variety of solid nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Superiority of electrolytic spray (direct ionization of noble metals from the corresponsing electrodes by electrochemical corrosion) and electrospray (ionization of metal ions from its precursor salts) to make metal NPs over previous methods lies in the fact that they do not involve any components other than the metal precursors. This ambient and direct method of synthesis is less expensive in comparison to processes like physical vapor deposition (PVD) (used for synthesis of metal NPs) , as no sophisticated instrumentation is used. Most important advantage of this method is that it can be performed at room temperature in air.…”
Section: Introductionmentioning
confidence: 99%